Lead (Pb) Contamination in Sediments and the Potential of Gastropods as Bioindicators of Pb in Mangrove Forests, Mojo Village, Pemalang - Latupeirissa, Cherokee Mikha-El; Haryati, Ani; Winanto, Tjahjo; Fikriyya, Nabela; Prihatiningsih, Isnaini; Januar, Hedi Indra; Putri, Wike Ayu Eka (Jurnal Kelautan Tropis, 2025)
The Mojo Village mangrove forest in Pemalang has undergone environmental degradation due to land conversion into shrimp farming areas. This conversion has led to increased anthropogenic activities, which are potential sources of heavy metal contamination in the waters, particularly lead (Pb). This study aimed to analyse Pb concentrations in sediments and gastropods and assess the potential of gastropods as bioindicators of Pb pollution. Sample preparation followed the USEPA 3051 method, and Pb analysis was conducted using Atomic Absorption Spectrophotometry (AAS). The results identified five gastropod species: Littoraria melanostoma, Littoraria scabra, Cerithidea cingulata, Cerithidea obtusa, and Cerithidea decollata. Pb concentrations in sediments averaged 11.86 ± 1.24 mg/kg, while in gastropods, the average was 0.43 ± 0.16 mg/kg. Although Pb levels in sediments indicate low contamination and no pollution, they may still pose potential biological risks. Cerithidea cingulata and Cerithidea obtusa were categorized as deco-concentrators with the potential to serve as bioindicators of Pb pollution. The study also revealed a very strong correlation between Pb concentrations in sediments and gastropods.